# What is the equation of the line normal to # f(x)=(x-1)(x+2)^2 # at # x=1#?

Expanding the brackets

By signing up, you agree to our Terms of Service and Privacy Policy

The equation of the line normal to f(x)=(x-1)(x+2)^2 at x=1 is y = -4x + 6.

By signing up, you agree to our Terms of Service and Privacy Policy

- What is the normal to the tangent line at the y-intercept to #y = 1/3x^3 - 4x + 2#?
- What is the equation of the tangent line of #f(x) =e^x/x-e^(2x-3)/x^3# at #x=2#?
- What is the equation of the tangent line of #f(x) =-2x^3+6x^2+2x-3# at #x=3#?
- How do you find the equation of the line tangent to #y=-x^2# at (0,0)?
- How do you find the instantaneous slope of #y=4-x^2# at x=1?

- 98% accuracy study help
- Covers math, physics, chemistry, biology, and more
- Step-by-step, in-depth guides
- Readily available 24/7